Effect of Production on Income and Feasibility of Hybrid Corn Farming in Sidondo I Village, Sigi Biromaru District, Sigi Regency - Endah Wahyuning Asih (International Journal of Health, Economics, and Social Sciences (IJHESS), 2021)
Corn is one of the crops that farmers in Indonesia widely cultivate, especially in Sidondo I Village, Sigi Biromaru District, Sigi Regency. Corn is the second most important food ingredient after rice. How much and how is the effect of hybrid corn production on the income and feasibility of hybrid corn farming in Sidondo I Village, Sigi Biromaru District. Based on the description of the discussion above, it can be concluded that: The size of the hybrid corn production greatly influences the income and feasibility of hybrid corn farming in Sidondo I Village, Sigi Biromaru District, Sigi Regency, as the average cost is IDR 4,482,814 or IDR 5,212,574, - per hectares in one growing season. With an income of Rp. 20,538,000 or Rp. 23,881,395- per hectare in one growing season, so the income of hybrid corn farmers at Rp. 4,500/kg is Rp. 16,055,186 or Rp. 18,668,821/ha. The average amount of R/C is 4.6. For each expenditure of Rp. 1.00, the revenue is Rp. 460 with a profit of Rp. 360. Thus, maize farming in Sidondo I Village, Sigi Biromaru District, Sigi Regency is feasible.